Strategic Learning Management and Transformational Leadership in Shaping Inclusive School Culture: A Systematic Literature Review of Educational Sociology - Arip Amin; Ali Miftakhu Rosyad; Aip Syarifudin; Muaz; Raisalam D. Angoy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine how the transformational leadership of school principals fosters an inclusive school climate, how strategic learning management enhances teachers’ capacity to respond to student diversity, and how the integration of both contributes to the development of a sustainable inclusive ecosystem. The study employed a systematic literature review method following the PRISMA guidelines. A total of 42 articles were selected from 847 search results retrieved from Scopus, Web of Science, and Google Scholar published between 2015 and 2024. The data were analyzed using thematic synthesis through systematic coding, categorization, and cross-study comparison to identify patterns of leadership practices, learning management strategies, and the construction of inclusive school culture. The findings reveal a consistent and substantial positive relationship between transformational leadership practices and inclusive learning management. Leadership interventions were found to function as strategic mediators in strengthening teachers’ adaptive capacity toward student diversity and in shaping an inclusive school culture. Furthermore, the synthesis highlights that effective collaboration between leadership and learning management practices supports the sustainability of inclusive education ecosystems. Based on these findings, this study proposes a comprehensive inclusive synergy model that extends Pierre Bourdieu’s theory of habitus and social capital within the context of inclusive schools in Indonesia.